Changing nature of religious rights under international law - Evans, Malcolm D. (Malcolm David), 1959-; Petkoff, Peter; Rivers, Julian (Oxford : Oxford University Press, 2015)
The right to freedom of religion or belief has become a matter of increasing controversy, both politically and in international law. This book provides a detailed assessment of the right in its contemporary context, analysing its current status, the impact of the 1981 United Nation's declaration, and the challenges facing the continued existence of the right.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on March 24, 2015).
Keywords: Freedom of religion (International law); Human rights -- Religious aspects